Morphological and performance characteristics as drop-out indicators in female gymnasts - Claessens, A. L; Lefevre, J. (The Journal of Sports Medicine and Physical Fitness, 1998)
BACKGROUND: Aim of this study was to investigate if morphological and performance characteristics are significant indicators to predict drop-out in female gymnasts. METHODS: Experimental design: comparative investigation between two groups of female gymnasts at the start of a 3-year follow-up period. Setting: participants of the study came from two gymnastic clubs from the Antwerp region in Flanders, Belgium. Participants: in total, 81 female competitive gymnasts (mean age: 10.5 + 2.6 years) were investigated, of which 46 were continuing gymnasts, while 35 dropped-out from the sport during the following 3 years. Measures: included were a large battery of a anthropometric characteristics, skeletal maturation, physical fitness tests, and gymnastic-specific strength and flexibility tests. Differences between the two groups were analysed by means of the t-test and analysis of co-variance with chronological age as the co-variate. RESULTS: Compared to the gymnasts, the drop-outs were significant (p < 0.01) older (11.3 and 9.7 years respectively), more mature (skeletal ages are 10.6 and 9.4 years respectively), taller (143.5 cm and 135.2 cm respectively), and heavier (36.0 kg and 29.4 kg respectively). Also for almost all other anthropometric dimensions, gymnasts were significantly (p < 0.01) smaller than the drop-outs, except for the biceps, triceps, medial calf, and thigh skinfolds. Concerning the fitness and gymnastic-specific test characteristics, the drop-outs performed also significantly (p < 0.01) better than the continuing gymnasts. The ANCOVA-analysis, however, revealed that it was mainly the age factor that distinguished both groups. After controlling for chronological age, no differences between both groups could be demonstrated for almost all anthropometric and performance characteristics with the exception for upperarm circumference flexed, calf circumference, and biceps skinfold. For these variables, drop-outs showed still significant (p < 0.05) higher values compared to the gymnast's group. CONCLUSIONS: Based on these findings, it is concluded that factors related to the physical make-up and performance capacities of our gymnasts under study are minor indicators for the withdrawal from competitive gymnastics, and it is hypothesized that the social and psychological factors associated with the older age of the drop-out girls are presumably more important.